Sistem Absensi Kegiatan Ormawa Berbasis QR Code - Suryawan, I Wayan Dharma; Ardhiana, Dewa Putu Yudhi (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2020)
The attendance system has an important role in everyday life, for example in schools, universities, factories, offices, hospitals, and other places that require attendance. Various efforts have been made so that the recording of attendance can be done easily and quickly. Efforts have been made, for example, by using fingerprints, RFID, and using QR codes. This study develops an attendance system for student organizations by using a QR code. There are two applications developed, namely a web-based system and a mobile-based system. Data management is carried out on a web-based system. Attendance input is done on a mobile-based system. Attendance input is done using a QR code. The database used is designed to maintain data integrity to minimize recording errors. The attendance system for ormawa activities has been successfully developed. The use of a QR code makes inputting timesheets easier and faster. Users simply scan the QR code to enter the timesheet.